Nanotubular crystals of garnierite Ni₆ (OH)₈[Si₄O₁₀] - Smolikov, A.; Vezentsev, A.; Beresnev, V.; Pavlenko, V.; Zagorodniuk, L.; Turbin, P. (Вопросы атомной науки и техники, 2015)
The influence of nature of initial components on synthesis conditions and morphology of nanotubular crystals of garnierite (Ni-chrysotile) has been studied. The synthesis of garnierite based on SiO2, Ni(OH)2, and NiSiO3 has been implemented at temperature 673 K and pressure 98.1 MPa in the time interval of 12…15 hours. Nanotubes were formed with an outer diameter of about 20 nm, contained alkali (1…10% NaOH) or salt (0.5…3%). It was shown that the types of tubes “cone in cone” and “tube in tube” are forms appropriate for distilled water. The synthesis conditions and the size of garnierite nanotubes strictly correspond to the parameters, inherent to Mg-chrysotile.